Problem Pokok Dalam Reformasi Pendidikan Nasional - H., M. Fazlurrahman (Islam Kontemporer, 2016)
Concentration fully reform the institutional aspects and teaching, still remaining implicates fundamental problem that has not gotten way out until today. The fundamental problem in question is still ongoing inconsistencies between the various national education policy. The disharmony generate serious impacts in the process of education reform in the country after the collapse of the New Order. Especially for education stakeholders, this disharmony makes their confusion, how should education reform agenda is executed. They are confronted with education policies that substantially contradict or at least overlap with one another. Worse yet, stakeholders of education in educational institutions is not only confused, but also become a victim of unwanted effects (unintended impact) or wild effect (spillover impact) on the implementation of the policy. So is the Islamic education institutions and academic staff who manage these institutions, "forced" to accept other forms of discriminatory treatment as a result of the policy of disharmony.